Patrzenie poprzez fragmenty. Komiksowy dziennik Aleksandra Zografa "Pozdrowienia z Serbii" - Czaja, Justyna (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2012)
In his comic Greetings from Serbia. A Journal in Comics Written During the Conflict in Serbia, Aleksander Zograf’s choice of form is associated with the periodical form of the diary in drawings kept by the author. By means of a series of episodes, Zograf shows selected fragments of daily life in Serbia: the realities of living in a country under sanctions, being bombed by NATO aircraft, and struggling with post-war chaos. A characteristic feature of the anthology Greetings from Serbia. A Journal in Comics Written During the Conflict in Serbia is – in the words of the author – “observation through fragments”. The poetics of the fragment, the autonomization of the individual elements that comprise the open composition, and the breaking up of the plot’s cohesion are all associated with the worldview that emerges from Zograf’s comics. The reality observed turns out to be chaotic, incoherent and irrational. It becomes impossible to fully embrace or provide any overarching sense to the events, and thus fictionalize and express them by means of a traditional narrative form. By choosing the form of the comic book, and abandoning a comprehensive, ordered point of view, the author attempts to describe the whole by means of fragments.

W komiksie Pozdrowienia z Serbii. Dziennik komiksowy z czasów konfliktu w Serbii, Aleksandra Zografa wybór formy związany jest z wybór formy związany jest z cyklicznością komiksowego dziennika, który prowadzi autor. W kolejnych odcinakach autor ukazuje wybrane fragmenty serbskiej codzienności: rzeczywistość kraju objętego sankcjami, bombardowanego przez samoloty NATO, borykającego się z powojennym chaosem. Tym, co symptomatyczne dla antologii Pozdrowienia z Serbii. Dziennik komiksowy z czasów konfliktu w Serbii jest właśnie owo „patrzenie poprzez fragmenty”. Poetyka fragmentu, zautonomizowanie poszczególnych części odznaczających się otwartą kompozycją, rozbicie spoistości fabuły wiążą się z wizją świata, jaka wyłania się z komiksu Zografa. Obserwowana rzeczywistość okazuje się chaotyczna, niespójna i irracjonalna. Niemożliwe więc staje się ogarnięcie i przedstawienie całościowego sens zdarzeń, a tym samym sfabularyzowanie i ujęcie ich w tradycyjną formę narracyjną. Decydując się na wybór małej komiksowej formy, rezygnując z całościowego, porządkującego spojrzenia, rysownik podejmuje próbę opisu całości poprzez fragment.
Looking Throught Fragments. Aleksandar Zograf's comics diary “Regards From Serbia”
Justyna Czaja, Katedra Filmu, Telewizji i Nowych Mediów UAM, Patrzenie poprzez fragmenty. Komiksowy dziennik Aleksandra Zografa Pozdrowienia z Serbii, Looking Throught Fragments. Aleksandar Zograf's comics diary “Regards From Serbia”, „Images” 2012, vol. X: Microcosmos, red. A. Szpulak i W. Otto, nr 19, s. 57-65, ISSN 1731-450x, język: polski
Keywords: comics; comics diary; Aleksandar Zograf; Regards from Serbia; komiks; komiksowy dziennik; Pozdrowienia z Serbii